The Effect of Potato Starch Substitution on the Quality of the Cake Flower Shake - Jayusman, Yesi; Gusnita, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This study aims to analyze the effect of potato starch substitution on the quality of the cake with the addition of 20%, 40%, and 60% potato flour. This type of research is a pure experimental study with a completely randomized design method (RAL) consisting of 4 treatments and 3 repetitions. The object of this research is the cake flower shake with potato flour substitution as much as 20%, 40%, 60% of the quality of the cake flower shake. The technique of collecting data in this research was carried out by organoleptic tests given to 5 expert panelists, namely lecturers of Family Welfare Sciences, Padang State University. The independent variable in this study was potato starch. The dependent variable of this research is the quality of the cakes produced, including the shape, color, aroma, texture and taste. The data analysis technique used was Analysis of Variance (ANAVA) to analyze organoleptic test data. The data that has been obtained is then tabulated in tabular form and analyzed according to the test of each data. Then the data analysis was carried out, if the data obtained by Fcount was greater than Ftable, then it was continued with Duncan's test. The results of this study indicate that there is a significant effect on the color quality of the cake, while the quality of shape, aroma, texture, and taste cannot be significantly different. It can be concluded that the results of the best quality test for potato starch cake are in treatment (X3) with 60% potato flour substitution.